Pengaruh Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan - Muhamad Faozan Afandi; Andi Sopandi; Darmadi Darmadi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of work discipline and compensation on employee performance at PT. Delta Sukses Pratama, Cikokol Tangerang. A quantitative approach with an associative research method was employed. The population consisted of all 75 employees of PT. Delta Sukses Pratama, and since the population size was relatively small, a saturated sampling technique was applied, resulting in 75 respondents. Data were analyzed using simple linear regression, multiple linear regression, correlation coefficient analysis, coefficient of determination, t-test, and F-test. The findings reveal that work discipline has a positive and significant effect on employee performance, indicating that employees who consistently comply with organizational rules, procedures, and responsibilities tend to demonstrate higher levels of performance. Compensation also exerts a positive and significant influence on employee performance, suggesting that fair and appropriate rewards enhance employee motivation and productivity. Furthermore, work discipline and compensation simultaneously have a positive and significant effect on employee performance, contributing 55.7% to the variance in performance, while the remaining 44.3% is explained by other factors outside the research model. These findings emphasize that employee performance improvement requires not only strong disciplinary practices but also an effective compensation system that recognizes employee contributions.